Historical analysis of governance at the Inter-American Development Bank (IDB) - Díaz-Bonilla, Eugenio; Centurion, Miriam; Bisogno, Marcelo (Inter-American Development Bank, 2022)
To analyze the governance arrangements of an institution it is necessary to understand the history and reasons for its creation, which, among other things, define its nature and the basic pacts and agreements (with the power balances implied) among the main actors involved. This document shows how the IDB emerged from a centuries-long interaction between LAC countries and the United States, on economic, political, and military matters. That dialogue led to the consideration of several regional financial institutions, including the 1940 Inter-American Bank, which was the predecessor of both the World Bank and the IMF. After the IDB was created in 1959, that dialogue was extended since the 1970s to the current partners from Europe and Asia, making the bank a global institution.